Role of Teacher in Forming Experience of Intercultural Interaction in Students - V I Kazarenkov; - Rangelova Emiliya Milenkova; T B Kazarenkova (Peoples' Friendship University of Russia (RUDN University), 2014)
The article considers the role of the teacher in the realization of one of the significant aspects of the problem of forming the experience of intercultural interaction in higher school students. The significance of personal and professional resources of the higher school teacher for the effective development in the future experts the requirement for intercultural interaction, the experience of intercultural interaction is revealed. The separate directions and forms of the activity of the teacher aimed at forming in students the experience of intercultural interaction in socially-educational space of the higher school are presented.